Variational methods in optimum control theory - q; ScienceDirect eBooks (New York : Academic Press, 1968)
Variational methods in optimum control theory.
Front Cover; Variational Methods in Optimum Control Theory; Copyright Page; From the Preface to the Russian Edition; Contents; Chapter I. Fundamental Concepts of the Calculus of Variations; Chapter II. Generalizations of the Simplest Problem of Calculus of Variations; Chapter III. Applying the Euler Equation to the Solution of Engineering Problems; Chapter IV. Field Theory. Sufficient Conditions for an Extremum; Chapter V. Extremum Problem with Constraints; Chapter VI. Examples of the Application of Variational Methods; Appendix I: Historical Survey; Appendix II: Glossary; References.
Includes bibliographical references (pages 204-212) and indexes.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Elsevier
Keywords: Control theory; Calculus of variations; Calcul des variations; Systèmes, Analyse de; TECHNOLOGY & ENGINEERING -- Automation; TECHNOLOGY & ENGINEERING -- Robotics; Calculus of variations; Control theory; Electronic books